高中同儕寫作回饋的效度與效果探析 Peer Feedback on Writing in a High School: Analysis of the Validity and Effect - 陳美芳 Mei-Fang Chen; 黃楷茹 Kai-Ju Huang; 謝佳男 Chia-Nan Hsieh; 林宜駿 Yi-Chun Lin (National Taiwan Normal University, 2010)
本研究在探究高中同儕寫作回饋的效度與效果。研究對象為臺北市42名高一學生，學生在每次作文後為同儕作文評分與回饋，並進行作文改寫。研究蒐集資料包括學生作文、同儕回饋資料、自陳心得與專家教師評分。學生與專家評分一致性，九成以上符合大考中心不需複閱的水準，差異在1 級分以內之百分比平均為72.05%，顯示學生評量效度佳。學生回饋具多元性，除針對語言、結構和內容外，也能以讀者角色提出情感回應。學生接受回饋後改寫的作文分數雖呈微升，但並未達顯著差異。學生認為教師回饋比同儕更有幫助、文字回饋比分數有助益。同儕回饋影響的變異性比教師影響大，功能與教師不同；教師能進行專業評論並指引修改方向，同儕則能提供情感的肯定與共鳴。 The research explored the validity and the effect of peer feedback on writing of senior high school students. 42 first-grade students in a senior high school in Taipei were asked to score and give written feedback each time after they finished the writing assignment. Rewriting was the basis of the feedback proceeded. Data including the students' compositions, written feedbacks and remarks from the peer, statements of every participant, and grades from the expert teachers, were collected. The result showed the percentage consistence of the grades scored by the students and by the expert teachers was 72.05%. The students' feedback not only aimed at the language, the structure, and the content of the composition, but also proposed the sentimental response and the overall impression as a reader. The grades of rewriting according to the peer feedback assumed tendency of micro liter. However, it showed no significant effect on transfer of learning. Besides, the students believed feedback from the teachers could be much helpful than the peer. Feedback of written words helped more than grades of numbers. The variance of peer feedback was greater than that of teachers. Finally, peer feedback functioned differently from teacher feedback. While the teacher reviewed the article professionally and gave comments for revision, the peer feedback provided affection support and sympathetic chord.